2021
DOI: 10.21203/rs.3.rs-600247/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Apigenin Ameliorates Lead Acetate induced Hyperlipidemia, Hypothyroidism and Hypogonadism in Male Rats

Abstract: Lead (Pb) is an environmental pollutant and has detrimental effects on human health. Apigenin (APG) is a flavonoid that have antioxidant, anti-inflammatory, antiallergic, and cardioprotective effects and is presented as treatment of some diseases. The aim of the present study was to evaluate the probable protective effect of APG against Pb-induced toxicity in rats. Adult male rats were given either Pb (as lead acetate; 20 mg/kg) alone or in combination with APG (20 mg/kg) daily for 4 weeks by intraperitoneally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The increase in serum TSH levels produced by lead may be linked to structural injury of thyroid follicular cells due to the accumulation of lead in the thyroid gland. This is similar to Algefare et al [54], who observed that the elevation in serum TSH level induced by lead acetate is likely a response to the decrease in serum T4 and T3 levels in rats. Thyroid hormones play essential roles in the development of the central nervous system (CNS).…”
Section: Discussionsupporting
confidence: 90%
“…The increase in serum TSH levels produced by lead may be linked to structural injury of thyroid follicular cells due to the accumulation of lead in the thyroid gland. This is similar to Algefare et al [54], who observed that the elevation in serum TSH level induced by lead acetate is likely a response to the decrease in serum T4 and T3 levels in rats. Thyroid hormones play essential roles in the development of the central nervous system (CNS).…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the exposure to Al 2 O 3 NP s and/or PbAc decreased sperm count and sperm motility while it increased the abnormal sperm count. Comparable impaired sperm parameters were observed in rats exposed to Al 2 O 3 NP s [ 5 ] or PbAc [ 38 , 99 ]. The reduction in sperm motility was most likely caused by the influence of Al 2 O 3 NP s on mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%